VD_FINDINFO HC / 2014 / 190 vom 13. März 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, DEMEURE DU DÉBITEUR, RÉSILIATION ANTICIPÉE, EXPULSION DE LOCATAIRE | 257d CO, 271 CO, 138 al. 1 CPC (CH), 141 al. 1 let. a CPC (CH), 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)